Effectiveness of a Teaching Material: News-Based Teaching of Mount Ungaran (Biosaintifika: Journal of Biology & Biology Education, 2023)
The news-based teaching is a teaching material that contains news integrated with the results of exploring the biodiversity on Mount Ungaran for high school students in  Biology subject. Teaching materials were prepared based on the results of the needs analysis. Early observation of High School 12 Semarang students showed that Biology learning sources were still insufficient to achieve basic competence. This study aimed to develop valid news-based teaching material of Mount Ungaran Biodiversity using the research and development (RD) method for effective cognitive, psychomotor, and affective learning outcomes. The research method subjected the students of High School 12 Semarang to explore the biodiversity news of Mount Ungaran on the websites. Also, the students searched the information from Research Development (RD). The results showed that (1) news-based teaching material on Mount Ungaran biodiversity was valid and appropriate as a learning source (96%), (2) and it was effective to improve the students’ cognitive, psychomotor, and affective learning outcomes of biodiversity topic.